2018
DOI: 10.1016/j.jab.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of time dependent changes of T2* in medial meniscus under loading at 3T: A preliminary study

Abstract: Due to the internal structure of the knee joint, the ability to characterize and quantify the dynamic response of the meniscal tissue directly is highly problematic. The main purpose of this study was to investigate the behaviour of the meniscus under loading conditions. Four healthy young females were included. To obtain T2* values in the meniscus, the vTE sequence was used with 10 echoes ranging from 0.8 to 10.1 ms. Submilisecond first echo time is a great advantage of vTE sequence allowing for precise mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A significant increase with loading was seen in the T2 of the control group, while T2 increase was less frequently observed in subjects with OA. Hornakova et al [40] studied the T2* variation in meniscus of four healthy individuals and reported a constant significant increase of T2* after compression in the anterior horn of the medial meniscus up to 40 minutes after loading.…”
Section: Quantitative Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…A significant increase with loading was seen in the T2 of the control group, while T2 increase was less frequently observed in subjects with OA. Hornakova et al [40] studied the T2* variation in meniscus of four healthy individuals and reported a constant significant increase of T2* after compression in the anterior horn of the medial meniscus up to 40 minutes after loading.…”
Section: Quantitative Mrimentioning
confidence: 99%
“…In other research studies, miniature MRI-compatible loading devices were utilized to apply loads on human or animal cartilage specimens using screw-driven indenters fabricated from plastic parts [25,[60][61][62][63][64][65][66]. Recently, Hornakova et al [40] employed tightened rubber bands attaching to the subject's waist and feet for loading knees in vivo, while the applied forces could be measured using dynamometric insoles.…”
Section: Mri-compatible Loading Devicesmentioning
confidence: 99%
“…Given this sport’s repetitive loading of the knee joint 1 3 , marathon running may affect the condition of the cartilage, meniscus, and other relevant tissues. The meniscus is an integral part of the knee and is considered the second stabilizer of the knee joint 4 , 5 , playing an important role in shock absorption, joint stability, joint lubrication, load transmission, and maintenance of articular cartilage integrity 6 8 . The meniscus is also one of the most frequently injured parts of the knee joint 5 , 9 , 10 , so the integrity of the meniscus—in both shape and function—is critical for the long-term health of the knee 6 , 8 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it would be clinically significant if there is a correlation between marathon running exercise and the physiologic state and injury of the knee meniscus. Recent studies have shown that quantitative magnetic resonance imaging (MRI) methods, such as T1/T2/T2* mapping or T1rho mapping, are helpful for continuous assessments of meniscal conditions and early detection of meniscal degeneration 3 , 5 8 , 14 16 . Furthermore, MRI has become integral for the diagnosis and treatment strategy of knee pathology 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated volume and thickness changes of meniscal tissue when comparing unloaded with loaded conditions ( Vedi et al, 1999 ; Tibesku et al, 2004 ; Kessler et al, 2006 ), while other MRI studies addressed meniscal movement during weight-bearing and knee flexion ( Thompson et al, 1991 ; Vedi et al, 1999 ; Kawahara et al, 2001 ; Boxheimer et al, 2004 ; Tibesku et al, 2004 ; Tienen et al, 2005 ; Yao et al, 2008 ). Recently, quantitative MRI parameters, including T1ρ and T2 relaxation times, have been evaluated to study the biochemical composition and structural changes of meniscal tissue due to progressive OA ( Son et al, 2013 ; Subburaj et al, 2015 ; Calixto et al, 2016 ; Hornakova et al, 2018 ). MRI has also been used to evaluate the extrusion of menisci in healthy and degenerated knee joints ( Berthiaume et al, 2005 ; Stehling et al, 2012 ; Patel et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%